PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 1 SUNGAI APIT - Zaleha '; Rini '; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research has been done to apply the cooperative learning type Round Table to improve student learning outcome on hydrocarbon subject in class X SMA Negeri 1 Sungai Apit. The research is a kind of experimental research with pretest-postest design. The samples of this research were the students of class X1 as the experimental class and students of class X3 as the control class is determined randomly after the normality test and homogenity test. Experimental class is a class that is applied model of cooverative learning type Round Table, while the control class wasnot treated by cooperative learning type Round Table. Data analysis technique used is the –t test. Based on analysis of data obtained tarithmetic ˃ ttable is 3,16˃ 2,00, means that type of cooperative learning model can improve student learning outcome on the subject hydrocarbon in class X SMA Negeri 1 Sungai Apit. The category of improvement student achievement in experiment class was high category with a gain score normalized is 0,77.Key Words : Cooperative Learning type Round Table, Learning Outcome, Hydrocarbon.